(Pre) Iron Age Burials of Thandikudi, Tamil Nadu. (12th May 2015) - Kumaran, R.N.; Saranya, M.
Thandikudi, one of the major villages in the Lower Palani Hills occupies a unique position as this village was well connected by major trade routes. The archaeological vestiges unearthed here have clearly attested that it was continuously occupied since pre-Iron Age times. The occurrence of Dolmens, Cists, Cairn-circles and Urns points out to the convergence of different cultural traits. The available data accumulated through the explorations and excavations gives an idea in drawing of cultural process of Palani hills, particularly of Thandikudi, which played an active role in trade during the medieval period as attested by trade guild inscriptions. The present study was also conducted to have an idea about the architectural achievement in stone working, constructional methods, engineering skills and technological perfection of the Iron Age builders.